The Duterte administration’s appeasement policy on China and the crisis in the Philippine–US alliance - de Castro, Renato Cruz (Animo Repository, 2017)
This article examines the shifts in Philippine foreign policy under the Duterte Administration, and how these changes impact 21st century Philippine–US alliance. Unlike the Aquino Administration that challenged China’s expansionism in the South China Sea, the Duterte Administration keeps silent on this maritime dispute in exchange for Chinese trade concessions, aid, and investments. President Duterte fosters closer economic and diplomatic relations with China and distances the Philippines from the US Specifically, he seeks China’s assistance for the building of drug-rehabilitation centers for Filipino drug dependents, soft loans for the construction of railways in Mindanao, and even the acquisition of Chinese-made weapons for the Armed Forces of the Philippines (AFP). In consideration of this largess, President Duterte has degraded the country’s strategic security ties with the US by terminating the joint Philippine–US naval patrols in the South China Sea, and limiting the scope and number of US military interactions with the AFP. These moves, which are a dramatic departure from the Philippines’ long-standing policy of maintaining close security ties with the US, have strained the Philippine–US alliance. This article addresses this central question: How do the foreign policy changes under the Duterte Administration adversely impact the Philippine–US alliance? It also raises the following questions: (1) What are the foreign policy goals of the Duterte Administration? (2) How does the Duterte Administration pursue these goals? (3) In what ways does the pursuit of these goals affect Philippine–US alliance? (4) What is the future of Philippine–US alliance in the light of the Duterte Administration’s shifting foreign policy goals? © 2017 Philippine Political Science Association (PPSA).